Association of zinc intake & serum zinc levels with acne severity - Otami, Chintia; Chandra, Novita; Sitohang, Irma Bernadette S. (UI Scholars Hub, 2020)
Background: Recent studies have suggested the relationship between diet and acne, and zinc plays a role through its anti-inflammatory mechanism. This study aimed to determine the association between zinc intake and serum zinc levels with acne severity. Methods: A comparative cross-sectional study was conducted to assess the difference in zinc intake and serum zinc levels with acne severity based on Indonesian Acne Expert Meeting (IAEM) criteria. Sixty patients with acne in Dr. Cipto Mangunkusumo General Hospital were selected. The effect of zinc intake on acne severity was analyzed via unpaired T test, whereas the effect of serum zinc levels on acne severity was examined with Mann–Whitney test. Data were further evaluated using SPSS 20.0. Results: Zinc intake in all the subjects was below the Indonesian recommended daily allowance, and the mean of zinc intake and serum zinc levels in the mild acne group was higher than that of the moderate–severe acne group. The zinc intake significantly differed between the mild and moderate–severe acne groups (p < 0.01). Likewise, serum zinc levels significantly varied between mild and moderate–severe acne group (p = 0.048). Conclusion: Although this study showed a significant difference between zinc intake and serum zinc levels with the severity of acne vulgaris, further follow-up studies should be performed to assess zinc for acne vulgaris therapy.